2020
DOI: 10.1002/aic.17007
|View full text |Cite
|
Sign up to set email alerts
|

Structured Ni@NaA zeolite supported on silicon carbide foam catalysts for catalytic carbon dioxide methanation

Abstract: Carbon dioxide (CO 2) conversion is an important yet challenging topic, which helps to address climate change challenge. Catalytic CO 2 methanation is one of the methods to convert CO 2 , however, it is limited by kinetics. This work developed a structured Ni@NaA zeolite supported on silicon carbide (SiC) foam catalyst (i.e., Ni@NaA-SiC), which demonstrated an excellent performance with a CO 2 conversion of 82%, being comparable to the corresponding equilibrium conversion, and CH 4 selectivity of 95% at 400 C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 46 publications
(83 reference statements)
1
9
0
Order By: Relevance
“…Additionally, the thin coating of S1 zeolite on the surface of SiC foam might also reduce the local diffusion resistance (across the catalytic layer) and improve the dispersion of Ni active sites, enabling the comparatively high activity achieved by the structured Ni/S1‐SiC and Ni@S1‐SiC than the pelletized Ni/S1 catalysts (which has low bed porosity and high diffusion resistance). Such phenomena have been confirmed by previous studies on structures foam catalysts 27,35,37 . Generally, the structured encapsulated Ni catalysts on SiC foams (Ni@S1‐SiC) presented significantly improved activity, as well as the H 2 /CO molar ratio (especially at ≥700°C), in comparison with the pellets packed bed (Ni/S1) and the structured Ni/S1‐SiC catalyst with the conventionally supported Ni species.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Additionally, the thin coating of S1 zeolite on the surface of SiC foam might also reduce the local diffusion resistance (across the catalytic layer) and improve the dispersion of Ni active sites, enabling the comparatively high activity achieved by the structured Ni/S1‐SiC and Ni@S1‐SiC than the pelletized Ni/S1 catalysts (which has low bed porosity and high diffusion resistance). Such phenomena have been confirmed by previous studies on structures foam catalysts 27,35,37 . Generally, the structured encapsulated Ni catalysts on SiC foams (Ni@S1‐SiC) presented significantly improved activity, as well as the H 2 /CO molar ratio (especially at ≥700°C), in comparison with the pellets packed bed (Ni/S1) and the structured Ni/S1‐SiC catalyst with the conventionally supported Ni species.…”
Section: Resultssupporting
confidence: 81%
“…The samples were pre‐reduced at 700°C for 1 hr in a 10% H 2 /Ar flow (at 30 ml/min) and then cooled down to 50°C. The H 2 pulse chemisorption was then carried out by pulsing of a mixture of 10% H 2 /Ar (30 ml/min), details are described elsewhere 27 . Thermogravimetric analyses (TGA) were performed using a thermogravimetric analyser (TGA 550) in the temperature range of 30–800°C with a heating rate of 10°C/min in an air atmosphere (30 ml/min).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking advantage of literature evidence for enhanced-CO 2 sorption properties of Ni catalysts on hydrophilic zeolite 5A, 340−344 Chen and coworkers have recently proposed the combination of SiC opencell foams functionalized with an homogeneous hydrophilic NaA coating layer to enhance the Ni catalyzed methanation. 345 Their structured catalyst reduced the mass and heat transfer effects of the process, hence shifting the reaction equilibrium toward CH 4 formation. Kinetic studies shown that besides a high stability of the structured catalyst (15 wt % Ni@NaA-SiC) on long-term methanation runs (>80 h at T = 400 °C, H 2 /CO 2 = 4, flow rate = 50 mL (STP) min −1 , GHSV = 1875 h −1 ; CO 2 conversion ≈82% and CH 4 selectivity ≈95%), the latter exhibited an appreciably lower activation energy (E a ≈ 30 kJ mol −1 ) compared to its SiC-free, pelletized counterpart (15 wt % N@NaA; E a ≈ 84 kJ mol −1 ).…”
Section: Catalytic Applicationsmentioning
confidence: 99%
“…Ni catalysts supported on LTA zeolite (sodium form, NaA)-coated SiC foams (Ni@NaA-SiC) have been used as catalysts for intensifying CO 2 methanation reaction. Taking advantage of literature evidence for enhanced-CO 2 sorption properties of Ni catalysts on hydrophilic zeolite 5A, Chen and co-workers have recently proposed the combination of SiC open-cell foams functionalized with an homogeneous hydrophilic NaA coating layer to enhance the Ni catalyzed methanation . Their structured catalyst reduced the mass and heat transfer effects of the process, hence shifting the reaction equilibrium toward CH 4 formation.…”
Section: Catalytic Applicationsmentioning
confidence: 99%